Ensino de relações numéricas com o uso de discriminações condicionais para crianças com Transtorno do Espectro Autista - Garcia, Rafael Vilas Boas (Universidade Federal de São Carlos, 2016)
The purposes of this research are evaluate the effectiveness of MTS computerized teaching tasks, and develop, apply and evaluate a Stimulus Equivalence Paradigm based curriculum to teach number concept. Studies that used MTS procedure to teach arbitrary conditional discriminations and equivalence relations obtained positive results on subjects with disability. We propose a systematic replication of Rossit (2003), that used MTS tasks to taught monetary system to youths with intellectual disability on a Stimulus Equivalence Paradigm based organized curriculum. In order to teach number concept, the experimental stimuli (numerals from one until nine, and figures of non-representational forms) were divided in three stimuli groups of increasing values in a multiple baseline design among stimuli groups. Were the participants in the research three ASD students with eight to 12 years old. The results shows efficacy on teach number concept for ASD children with strategy derived of Stimulus Equivalence, replicating the results obtained by Rossit (2003) and corroborating with previous notes on the contribution of resource derived from the Applied Behavior Analysis for the successful in inclusion of students with ASD.
Keywords: Equivalência de estímulos; TEA; Ensino de matemática; Stimulus equivalence; ASD; Math teaching; CIENCIAS HUMANAS::EDUCACAO